2016 IEEE Third Underwater Communications and Networking Conference (UComms) 2016
DOI: 10.1109/ucomms.2016.7583420
|View full text |Cite
|
Sign up to set email alerts
|

The DESERT underwater framework v2: Improved capabilities and extension tools

Abstract: The DESERT Underwater emulation system (http://nautilus.dei.unipd.it/desert-underwater), originally designed for testing underwater acoustic networks, has been recently extended. The new framework now includes multi-modal communication functionalities encompassing low rate and high rate acoustics as well as optics, the capability of testing wireless telemetry for underwater equipment, a connection to the most recent version of the World Ocean Simulation System (WOSS), a modification to the RECORDS system for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 20 publications
(26 reference statements)
0
31
0
Order By: Relevance
“…Both the control station and HROV were equipped with MF, HF acoustic, and optical modems, while the acoustic relays were equipped only with MF acoustic modems. All simulations were performed with the DESERT Underwater [117] simulation framework. As presented in Section 2.4, we selected the BlueComm 200 optical modem, Subnero WNC, and the EvoLogics S2C HS communication devices; therefore, the simulations were configured according to the modem specifications, as will be presented later in this section and is summarized in Table 5.…”
Section: Scenario Description and Simulation Setupmentioning
confidence: 99%
“…Both the control station and HROV were equipped with MF, HF acoustic, and optical modems, while the acoustic relays were equipped only with MF acoustic modems. All simulations were performed with the DESERT Underwater [117] simulation framework. As presented in Section 2.4, we selected the BlueComm 200 optical modem, Subnero WNC, and the EvoLogics S2C HS communication devices; therefore, the simulations were configured according to the modem specifications, as will be presented later in this section and is summarized in Table 5.…”
Section: Scenario Description and Simulation Setupmentioning
confidence: 99%
“…There are also multiple UAN simulation suites that focus on providing a seamless transition between testing the network performance in simulation and testing the developed protocols at sea using real hardware. Two notable examples of such simulation suites are DESERT [23] [49] and SUNSET [24]. Both of these simulators are based on the ns2-MIRACLE network simulation platform and both have been verified to successfully facilitate the transition from simulation to at-sea testing using real acoustic modems [47] [24]; however, an investigation by Petroccia and Spaccini [41] showed that SUNSET provides a more mature and efficient solution for transitioning from simulation to real-time at-sea implementation.…”
Section: State-of-the-art In Underwater Acoustic Channel Simulationmentioning
confidence: 99%
“…There are also multiple UAN simulation suites that focus on providing a seamless transition between testing the network performance in simulation and testing the developed protocols at sea using real hardware. Two notable examples of such simulation suites are DESERT [23] [46] and SUNSET [24]. Both of these simulators are based on the ns2-MIRACLE network simulation platform and both have been verified to successfully facilitate the transition from simulation to at-sea testing using real acoustic modems [44] [24]; however, an investigation by Petroccia and Spaccini [34] showed that SUNSET provides a more mature and efficient solution for transitioning from simulation to real-time at-sea implementation.…”
Section: State-of-the-art In Underwater Acoustic Channel Simulationmentioning
confidence: 99%